The Complexity of the IGF1 Gene Splicing, Posttranslational Modification and Bioactivity - Philippou, Anastassios (ScholarOne, 2014)
The insulinlike growth factor-I (IGF-I) is an important factor which regulates a variety of cellular responses in multiple biological systems. The IGF1 gene comprises a highly conserved sequence and contains six exons, which give rise to heterogeneous mRNA transcripts by a combination of multiple transcription initiation sites and alternative splicing. These multiple transcripts code for different precursor IGF-I polypeptides, namely the IGF-IEa, IGF-IEb and IGF-IEc isoforms in humans, which also undergo posttranslational modifications, such as proteolytic processing and glycosylation. IGF-I actions are mediated through its binding to several cell-membrane receptors and the IGF-I domain responsible for the receptor binding is the bioactive mature IGF-I peptide, which is derived after the posttranslational cleavage of the pro-IGF-I isoforms and the removal of their carboxy-terminal E-peptides (that is, the Ea, Eb and Ec). Interestingly, differential biological activities have been reported for the different IGF-I isoforms, or for their E-peptides, implying that IGF-I peptides other than the IGF-I ligand also possess bioactivity and, thus, both common and unique or complementary pathways exist for the IGF-I isoforms to promote biological effects. The multiple peptides derived from IGF-I and the differential expression of its various transcripts in different conditions and pathologies appear to be compatible with the distinct cellular responses observed to the different IGF-I peptides and with the concept of a complex and possibly isoform-specific IGF-I bioactivity. This concept is discussed in the present review, in the context of the broad range of modifications that this growth factor undergoes which might regulate its mechanism(s) of action.